2021
DOI: 10.1101/2021.03.22.436280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete loss of CASK causes severe ataxia through cerebellar degeneration in human and mouse

Abstract: Heterozygous loss of X-linked genes like CASK and MeCP2 (Rett syndrome) causes neurodevelopmental disorders (NDD) in girls, while in boys such loss leads to profound encephalopathy. The cellular basis for these disorders remains unknown. CASK is presumed to work through the Tbr1-reelin pathway in neuronal migration during brain development. Here we report our clinical and histopathological analysis of a deceased 2-month-old boy with a CASK-null mutation. We demonstrate that although smaller in size, the CASK-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In contrast to girls, who have two alleles of the CASK gene, hemizygous boys with CASK loss-of-function variants present with a more severe phenotype. In addition to MICPCH, they are also diagnosed with epileptic encephalopathies such as Ohtahara syndrome and West syndrome (infantile spasms) due to the presence of early-onset epilepsy and diagnostic EEG (electroencephalogram) patterns such as burst-suppression and hypsarrhythmia [ 35 , 36 , 37 , 38 ]. Boys with mosaic variants in CASK that arise during embryogenesis present with MICPCH, just like girls [ 33 , 35 ].…”
Section: Micpch and Cask -Linked Pathologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to girls, who have two alleles of the CASK gene, hemizygous boys with CASK loss-of-function variants present with a more severe phenotype. In addition to MICPCH, they are also diagnosed with epileptic encephalopathies such as Ohtahara syndrome and West syndrome (infantile spasms) due to the presence of early-onset epilepsy and diagnostic EEG (electroencephalogram) patterns such as burst-suppression and hypsarrhythmia [ 35 , 36 , 37 , 38 ]. Boys with mosaic variants in CASK that arise during embryogenesis present with MICPCH, just like girls [ 33 , 35 ].…”
Section: Micpch and Cask -Linked Pathologiesmentioning
confidence: 99%
“…Overall the phenotype indicates that the role of the CASK gene itself does not have any sex-specificity, but rather that differences in phenotype between girls and boys arise simply due to the fact that in boys there is only one X-chromosome and hence one CASK gene. Analysis of boys with CASK -null variants suggests that the lethality observed in boys is due to thinning of the brain stem which leads to aberrant respiratory and deglutition reflexes manifesting systemically as central neurogenic respiratory failure, airway infection, and pneumonia [ 35 , 36 , 37 ]. A previously published histopathology of a posthumous CASK -variant case suggested that there could be defects in cortical and cerebellar layering, indicating a defect in neuronal migration.…”
Section: Micpch and Cask -Linked Pathologiesmentioning
confidence: 99%
See 3 more Smart Citations